Combination of electromagnetic navigation bronchoscopy‐guided microwave ablation and thoracoscopic resection: An alternative for treatment of multiple pulmonary nodules. Issue 6 (14th April 2020) - Jiang, Ning; Zhang, Liming; Hao, Yingtao; Wu, Xiaolin; Zhao, Yunpeng; Cong, Bo; Peng, Chuanliang
Abstract : Here, we describe a novel method using microwave ablation (MWA) guided by electromagnetic navigation bronchoscopy (ENB) and video‐assisted thoracoscopic surgery (VATS) for simultaneous treatment of multiple high‐risk pulmonary nodules in a 47‐year‐old woman. After the ENB registration process, the operator delivered the locatable electromagnetic probe to the target in the right upper lobe following the navigational route. MWA was performed after an antenna was passed into the lesion through the working channel. The wedge resection of the left upper lobe and lower lobe and the lingual segment resection were performed by VATS. The pathological diagnoses was adenocarcinoma in situ (AIS) of the right upper lobe lesion, AIS of the left upper lobe, minimally invasive adenocarcinoma of the left lower lobe lesion and chronic inflammation of the lingular segment. MWA guided by ENB combined with VATS is an alternative treatment strategy to deal with multiple pulmonary nodules at the same stage of the operation.